Penetration of cefluprenam into wound exudate and bile, and clinical studies of cefluprenam for surgical application - Yokoyama, Isao; Nohga, Katsuhiko (Japanese Journal of Chemotherapy, 1995)
We investigated the clinical efficacy of cefluprenam (CFLP), a newly developed injectable antibiotic, against various surgical infections.We also studied the drug distribution into wound exudate and bile. The CFLP concentrations in exudate were 13.4±3.2 μg/ml after 1 hour and 6.26μg/ml after 6 hours.The concentration of CFLP in bile was 23.8μg/ml after 1 hour with 30 min drip infusion of 1 g of CFLP. The clinical efficacy of CFLP was evaluated in 10 cases.There was seen good in all cases.The bacteriological response was investigated in 14 strains Gram-positive bacteria (6 strains), Gram-negative bacteria (5 strains), and anaerobes (3 strains) exhibiting 92.9 % of the eradication rate.Although no adverse drug reaction was recognaized, mild abnormal laboratory findings were noted in 1 case.